KERAGAAN PENGEMBANGAN ALSINTAN DAN USAHA PELAYANAN JASA ALSINTAN UNTUK USAHATANI PADI DI LAHAN SAWAH KABUPATEN HALMAHERA UTARA - Yopi Saleh; Chris Sugihono (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
ABSTRACTThe Performance of Agricultural Machinery Development and Service Business of Agricultural Machinery for Rice Farming in Lowland Areas North Halmahera District. Service Business of Agricultural Machinery (UPJA) was formed and directed as one of the economic driving forces in rural areas to improve agricultural production effisiency through agricultural mechanization. This study aims: (1) to analyze the performance of agricultural machinery development for rice farming in lowland areas, (2) to analyze the business opportunities of agricultural machinery services for rice farming in lowland areas, (3) to analyze the performance of UPJA development for rice farming in lowland areas. The study was conducted in September-December 2018 using census method to 12 UPJA in West Kao dan South Tobelo sub-districts, North Halmahera district. Data of agriculural machinery and UPJA development were arranged in tables and charts, then analyzed using requirement and adequacy of agricultural machinery analysis; investment feasibility analysis, and matrix performance analysis. The results showed that from the adequacy status, the number of hand tractor and big combine harvester was still inadequate, i.e. 51 units and 21 units respectively, while rice transplanter was already sufficient. From the economic indicators (NPV, B/C, IRR, and payback period), rental business of the three machines was feasible. However, rental business for hand tractor and big combine harvester through UPJA in North Halmahera was more feasible and it has a better prospects compared to rice transplanter. The performance of UPJA can be grouped into two groups namely beginner (66,67%) and developing (33.33%). The UPJA performance should be improved by improving management staffs and operators of agricultural machinery through training and supervision as well as optimalization of it’s agricultural machinery utilization.Key words: rice, agricultural machinery, service business, lowland, North Halmahera ABSTRAKUsaha Pelayanan Jasa Alat dan Mesin Pertanian (UPJA) dibentuk dan diarahkan sebagai salah satu penggerak kekuatan ekonomi di perdesaan untuk mendukung peningkatan efisiensi produksi pertanian melalui mekanisasi pertanian. Tujuan kajian adalah: (1) Menganalisis keragaan pengembangan alsintan untuk usahatani padi di lahan sawah, (2) Menganalisis peluang bisnis pelayanan jasa alsintan untuk usahatani padi di lahan sawah, dan (3) Menganalisis kinerja pengembangan UPJA pada usahatani padi di lahan sawah. Pengkajian dilakukan pada bulan September-Desember 2018 dengan metode sensus pada 12 UPJA di Kecamatan Kao Barat dan Kecamatan Tobelo Selatan, Kabupaten Halmahera Utara. Data alsintan dan UPJA yang diperoleh disusun dalam bentuk tabel dan bagan, kemudian dianalisis menggunakan analisis kebutuhan dan kecukupan alsintan; analisis kelayakan investasi, dan analisis matriks kinerja UPJA. Hasil kajian menunjukkan bahwa dari status kecukupannya, jumlah alsintan traktor roda 2 dan combine harvester besar masih sangat kurang, masing-masing sebanyak 51 unit dan 21 unit, sedangkan rice transplanter sudah memadai. Dari indikator ekonomi (NPV, B/C, IRR, dan payback period) ketiga alsintan tersebut layak diusahakan. Namun demikian, usaha jasa penyewaan traktor roda dua dan combine harvester besar pada UPJA di Kabupaten Halmahera Utara memiliki kelayakan usaha lebih tinggi dan prospek usaha lebih baik daripada rice transplanter. Kinerja UPJA di Kabupaten Halmahera Utara dapat dikelompokkan menjadi dua, yaitu: 66,67% UPJA pemula dan 33,33% UPJA berkembang. Kinerja UPJA perlu ditingkatkan dengan meningkatkan kemampuan SDM pengelolanya dan operator alsintan melalui pelatihan dan pendampingan serta optimalisasi pemanfaatan alsintan. Kata kunci: padi, alsintan, usaha jasa, lahan sawah, Halmahera Utara